Gray gas emissivities for H2O-CO2-CO-N2 mixtures. (November 2018) - Alberti, Michael; Weber, Roman; Mancini, Marco
Highlights: Procedure for calculating gray gas emissivities of H2 O-CO2 -CO-N2 -mixtures is given. EXCEL program is provided that calculates gray gas emissivities. Emissivities are within ± 1% margin if compared to line-by-line calculated values. New emissivity charts, similar to Hottel's graphs, have been generated. Abstract: Gray gas emissivities of water vapor, carbon dioxide, and carbon monoxide are needed in many engineering calculations to determine radiative heat fluxes in high-temperature processes. In this work we provide (a) an EXCEL program (see Supplementary Material) that predicts total gas emissivities for H2 O-CO2 -CO-N2 mixtures and (b) a set of graphs for calculations by hand (see Appendix). The EXCEL program uses pre-calculated emissivity charts and overlap correction charts to interpolate the total emissivity for given compositions, temperatures, and pressures. The interpolated emissivities differ by − 0.15 % ± 0.73 % on average if compared to spectral line-by-line calculations using HITEMP-2010 spectroscopic database. Differences in case of the well-known Hottel's emissivity charts are larger than 200%, particularly at high pressures. Emissivities calculated using Leckner's polynomials may differ from the line-by-line calculated values by −90%–180%.